(untitled) (Global Journals of Research in Engineering, 2022)
The mobile device manufacturers and Internet Of Things are searching for more compatible and easy to connect protocols that increase coverage, which generates the user an effective experience when using different devices. Nevertheless, the constant updating process opens a security gap that exposes the users’ personal information. Bluetooth is a communication protocol openly used by manufacturers because of their excellent information transfer capacities, allowing hackers to exploit it. The manufacturers work daily, generating security patches for communication protocols but this hasn’t been enough to mitigate vulnerabilities. The security has always been on the manufacturer’s side but the final user is limited to use a few security customization options to protect his network perimeter. Based on the wireless devices’ background we wonder, Is there any way in which the user has the chance to reduce the possible dangers that wireless devices face? We can answer this question through the development of a research in the more vulnerable areas, simulating the attacks on a mobile device to generate a possible solution that allows the user to have more control over his bluetooth connections.